"A murky business": A phenomenological ontology of risk in child protection social work. (March 2020) - Smeeton, Joe
This paper is based upon ongoing theoretical work by the author. A growing number of academics are starting to problematise social work within a risk paradigm by highlighting the impact this has on how service user's experiences are atomised into units of risk, rather than having their needs understood as members of families and communities. This paper seeks to develop this discussion by offering a theoretical examination of risk from a phenomenological perspective by unpacking some of the underlying constructions of risk. Using Heidegger's work this paper attempts to first of all undertake an ontology of risk and then to examine its usefulness in the UK child protection context. The author argues that working within a risk paradigm obscures rather than clarifies understanding. The approach is rooted in an argument that "phenomenology" is the natural home of social work which is interested in the lived experiences of people within their environments or "being-in-the-world".